2020
DOI: 10.5603/ep.a2020.0027
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumours in patients with von Hippel-Lindau disease

Abstract: Von Hippel-Lindau disease is a highly penetrant autosomal genetic disorder caused by a germline mutation in the tumour suppressor gene, manifesting with the formation of various tumours, including neuroendocrine tumours of the pancreas. The incidence of the latter is not very high, varying from 5% to 18%. To compare, haemangioblastomas and clear cell renal carcinoma are present in 70% of von Hippel-Lindau patients and are considered the main prognostic factors, with renal cancer being the most common cause of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…In a retrospective study, Zwolak et al ( 16 ) found that in the general population, PNETs in VHL have an estimated incidence of approximately 5–18%. However, PNETs comprise only 5% of pancreatic cancers and the association between PNETs and VHL is less than 0.5%.…”
Section: Resultsmentioning
confidence: 99%
“…In a retrospective study, Zwolak et al ( 16 ) found that in the general population, PNETs in VHL have an estimated incidence of approximately 5–18%. However, PNETs comprise only 5% of pancreatic cancers and the association between PNETs and VHL is less than 0.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Patients therefore require lifelong monitoring and management, which often includes multiple surgeries throughout their lives. Patients who undergo pancreatic surgery are at risk for several complications, including perioperative infections, development of diabetes mellitus, loss of exocrine function, and pancreatic fistulas ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 9% to 17% of patients with VHL disease will develop pNETs ( 3, 12 ). The prognosis for VHL disease–associated pNETs is generally favorable because pNETs are always nonfunctional and mostly asymptomatic ( 13–15 ). However, larger tumors have metastatic potential ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…DFI enabled the identification of small hypervascular lesions within 10 mm, which was unexpected (Figure 4c, 4d). The frame rate of DFI is higher than those of B-mode and eFLOW; thus, DFI can be used as a screening evaluation for patients with Multiple Endocrine Neoplasia type 1 or von Hippel-Lindau disease [39,40]. Hypersensitivity to vascular structures aided the avoidance of thick vessels during the EUS fine-needle biopsy (EUS-FNB) procedure (Figure 5).…”
Section: Discussionmentioning
confidence: 99%